2015
DOI: 10.1039/c4tb01573h
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost photo-responsive nanocarriers by one-step functionalization of flame-made titania agglomerates withl-Lysine

Abstract: A novel versatile photo-responsive nanocarrier that is able to load and release several functional molecules is obtained by one-step conjugation of scalable flame-made titania agglomerates. Highly crystalline anatase nano-crystals are synthesized by scalable flame spray pyrolysis of organometallic precursor solutions.Nanocarriers are self-assembled by adsorption of lysine molecules on the photocatalytic nanoparticles' surface leading to a minimal flocculation and highly reactive amine terminations. Time-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…[22] In contrast, all these absorption peaks were not present in both raw cotton and kapok, which contain only cellulose (in cotton) and lignin (in kapok). [19,23] XPS further confirmed the change of surface chemistry after PDA modification. We observed that only the peaks of C1s and O1s were observed in raw cotton and kapok, whereas a new peak of N1s appeared in both cotton@PDA and KP@PDA ( Figure 3C,D).…”
Section: Preparation Of Dual-superlyophobic Fiber Membranesmentioning
confidence: 77%
See 1 more Smart Citation
“…[22] In contrast, all these absorption peaks were not present in both raw cotton and kapok, which contain only cellulose (in cotton) and lignin (in kapok). [19,23] XPS further confirmed the change of surface chemistry after PDA modification. We observed that only the peaks of C1s and O1s were observed in raw cotton and kapok, whereas a new peak of N1s appeared in both cotton@PDA and KP@PDA ( Figure 3C,D).…”
Section: Preparation Of Dual-superlyophobic Fiber Membranesmentioning
confidence: 77%
“…[9] The colors of raw cotton and kapok fibers changed from white (cotton) and light gray (kapok) to dark brown, substantiating the growth of PDA on the fibers. [19] Moreover, the catechol and amine groups of PDA improved the hydrophilicity of kapok, which can be easily wetted by water and sunk into water after the modification (Figure S1, Supporting Information). [20] The chemical compositions of raw cotton, raw kapok, cotton@PDA, and KP@PDA were investigated by attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) and X-ray photoelectron spectrometer (XPS) analyses.…”
Section: Preparation Of Dual-superlyophobic Fiber Membranesmentioning
confidence: 99%
“…The optimized in-plane parameters for CrBr 3 , CrI 3 , silicene and germanene are 6.345, 6.875, 3.845 and 4.017 Å, which are consistent with previous reports. [11,29,41] The Ge/CrI 3 , Si/CrI 3 and Si/CrBr 3 heterostructure slabs are constructed by 3×3 Mene supercell to match the CrX 3 single-layer, and the lattice mismatch is 1.2%, 3.2% and 5.0%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…From the discharge curve measured with the two-electrode system, the energy density (E) and power density (P) were calculated as follows: [36] E ¼ I…”
Section: Electrochemical Measurementmentioning
confidence: 99%